Simple synthesis of reduced graphene oxide (rGO) from lignite via controlled carbonization temperature for energy storage electrodes (Kuwait Journal of Science)
Lignite coal was carbonized at 400 °C, 500 °C, and 600 °C to produce coalite samples, subsequently synthesized into reduced graphene oxide (rGO) using Hummer's method. The synthesized rGO was then fabricated as an electrode. This study examines how coalite carbonization temperature affects rGO synthesis as a sodium ion battery (SIB) cathode. Characterization results confirmed successful synthesis: X-ray diffraction (XRD) showed an amorphous structure with a 25° peak, Fourier Transform Infrared Spectroscopy (FTIR) identified key functional groups, and scanning electron microscopy-energy dispersive X-ray (SEM-EDX) mapping recorded the highest porosity (69.19 %) in the rGO 600 sample. Electrochemical tests (galvanostatic charge-discharge, cyclic voltammetry, and electrochemical impedance spectroscopy) demonstrated superior performance in the rGO 600 sample, achieving a specific capacity of 17.85 F/g, a power density of 41.82 W/kg, and an energy density of 0.197 Wh/kg. These results indicate a positive correlation between rGO porosity and electrochemical performance, supporting rGO from coalite as a promising material for future sustainable supercapacitors. © 2025